Comparative study of stress and strain partitioning behaviors in medium manganese and transformation-induced plasticity-aided bainitic ferrite steels. (15th March 2022) - Hojo, Tomohiko; Koyama, Motomichi; Kumai, Bakuya; Shibayama, Yuki; Shiro, Ayumi; Shobu, Takahisa; Saitoh, Hiroyuki; Ajito, Saya; Akiyama, Eiji
Abstract: The origins of the superior work hardening capability of medium manganese (M-Mn) and conventional transformation-induced plasticity-aided bainitic ferrite (TBF) steels of similar tensile strength and elongation are comparatively investigated via synchrotron X-ray diffraction measurements. The M-Mn steel undergoes preferential plastic deformation in austenite; its superior work hardening capability and associated uniform elongation are attributed to the high rates of martensitic transformation and dislocation accumulation per strain in the retained austenite. By contrast, the excellent work hardening behavior and uniform elongation of the TBF steel are attributed to the sustained transformability until the occurrence of a large strain and significant stress partitioning between the face-centered cubic (FCC) and body-centered cubic (BCC) phases due to the high austenite phase stability and high resistance to slip deformation of austenite. Graphical abstract: Image, graphical abstract